Oxidative and Nitrosative Stress and Immune-inflammatory Pathways in Patients with Myalgic Encephalomyelitis (ME)/Chronic Fatigue Syndrome (CFS) - Morris, Gerwyn; Maes, Michael (Current Neuropharmacology, 2014)
Myalgic Encephalomyelitis (ME) / Chronic Fatigue Syndrome (CFS) has been classified as a disease of the central nervous system by the WHO since 1969. Many patients carrying this diagnosis do demonstrate an almost bewildering array of biological abnormalities particularly the presence of oxidative and nitrosative stress (O&NS) and a chronically activated innate immune system. The proposal made herein is that once generated chronically activated O&NS and immune-inflammatory pathways conspire to generate a multitude of self-sustaining and self-amplifying pathological processes which are associated with the onset of ME/CFS. Sources of continuous activation of O&NS and immuneinflammatory pathways in ME/CFS are chronic, intermittent and opportunistic infections, bacterial translocation, autoimmune responses, mitochondrial dysfunctions, activation of the Toll-Like Receptor Radical Cycle, and decreased antioxidant levels. Consequences of chronically activated O&NS and immune-inflammatory pathways in ME/CFS are brain disorders, including neuroinflammation and brain hypometabolism / hypoperfusion, toxic effects of nitric oxide and peroxynitrite, lipid peroxidation and oxidative damage to DNA, secondary autoimmune responses directed against disrupted lipid membrane components and proteins, mitochondrial dysfunctions with a disruption of energy metabolism (e.g. compromised ATP production) and dysfunctional intracellular signaling pathways. The interplay between all of these factors leads to self-amplifying feed forward loops causing a chronic state of activated O&NS, immune-inflammatory and autoimmune pathways which may sustain the disease.
Keywords: oxidative